The may album - Esslinger, Reed; McRae, Collin; Lemi, Esthir (Loompianola project, 2014)
This is a collection of sounds from an experimental art piece that linked a Loom to a Piano. The result was a hybrid object that functioned both in music-making and weaving. It was up in May 2014, where the creators invited collaborators to come play with it. It was made by Reed Esslinger, Collin McRae, and Esthir Lemi. 'Strands in Descent' is a remix of recordings done by Simon Alexander-Adams, and 'Eterna' is a recording of a score by Esthir Lemi made specifically for the sculpture. Thank you to all of our generous supporters, and we look forward to being in touch about the next iteration of the Loompianola, which is in the making!creditsreleased September 26, 2014 Reed Esslinger, Collin McRae, Esthir Lemi, Eric Sheffield, Simon Alexander-AdamsLoompianola ÿwas conceived from a fascination with the shared lineage of a loom, a piano, and early computers. The Cranbrook Loom and Grinnell Brothers Player Piano each form a strong link to the ingenuity and industry of southeast Michigan; as a hybrid object, their taut strings pluck at each others original function and meaning. When activated by performers, the loom's warp and a piano's array of strings create music that is altered as the tapestry accumulates. Sensory technology embedded in the object activates a synergy of sonic, laborious, and playful movement.Drawing on the tradition of chamber music, a musical conversation among friends in the home, Loompianola fosters dialogue between not only distinct objects but three artists of various backgrounds: Collin McRae, an experimental musician and animator, Esthir Lemi, a composer, musical theorist, and new media artist, and Reed Esslinger, a performance artist and weaver. Like any organic conversation among friends, the language of Loompianola emerges organically from its operators.